Evaluation of repeated sprint test protocols used in soccer with a global positioning system - Kaan Kaya; Barış Gürol (Physical Education of Students)
Background and Study Aim. The aim of the research is to evaluate the 7x34.2 m Repeated Straight Sprint Test (RSST) and 7x34.2 m Repeated Change of Direction Sprint Test (RCST), which are used for improvement, measurement, and evaluation of repeated sprint ability, by using Global Positioning System (GPS).